2012
DOI: 10.1063/1.3679165
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing, coalescence, and separation in head-on collision of unequal-size droplets

Abstract: The dynamics of head-on collision of unequal-size droplets were experimentally and theoretically investigated, with emphasis on identifying distinct collision outcomes and interpreting the size-ratio dependence. A unified regime diagram in terms of bouncing, permanent coalescence, and separation after coalescence was identified for hydrocarbon and water droplets in the parameter space of the size ratio and a collision Weber number. Experimental results show that the transition Weber number, Web-c, that separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 15 publications
5
121
1
8
Order By: Relevance
“…The dominant phenomena in this stage are droplet collision, coalescence and deformation, which are similar to those observed in the collision of two nonreactive droplets [25,37] . A slightly dark "tail" behind the WFNA droplet is the shadow of NA vapor, which is negligible during this stage because of the relatively low droplet temperature and the short time.…”
Section: Descriptions Of Ignition Phenomenasupporting
confidence: 59%
See 1 more Smart Citation
“…The dominant phenomena in this stage are droplet collision, coalescence and deformation, which are similar to those observed in the collision of two nonreactive droplets [25,37] . A slightly dark "tail" behind the WFNA droplet is the shadow of NA vapor, which is negligible during this stage because of the relatively low droplet temperature and the short time.…”
Section: Descriptions Of Ignition Phenomenasupporting
confidence: 59%
“…Previous studies [25][26][27] have demonstrated that droplet separation is suppressed and hence droplet coalescence is promoted by increasing the size ratio. It is known that droplet separation occurs, at relatively high Weber numbers, when the surface tension of the temporarily coalesced droplet cannot hold the excess kinetic energy of the collision.…”
Section: Collision Dynamics and Internal Mixing Of Dropletsmentioning
confidence: 99%
“…With decreasing size ratio the boundary line is shifted remarkably to the right, to higher We. However, this is not in accordance with the studies of Tang et al (2012) where  = 0.4 results in a shift to Wec ~ 40. A shift of this boundary line to the right was also observed by Kuschel and Sommerfeld (2013) and Sommerfeld and Kuschel (2016) when increasing the dynamic viscosity of the liquid, similar to the work of Gotaas et al (2007).…”
Section: Theoretical Boundary Linescontrasting
confidence: 53%
“…One result of Rabe et al (2010) for different sized water droplets is also found in this region. This point is just included for illustrating the fact that decreasing size ratio yields a shift of the triple point as well as Wec to the right (see Tang et al 2012). The data points for the Diesel/water emulsion droplets are initially above and for higher water content, and hence larger viscosity, below the correlation, which suggests a slightly lower slope of such correlation (Chen et al 2017).…”
Section: Characteristic Points In the Collision Mapsmentioning
confidence: 99%
“…A similar variety of processes is observed for colliding drops: they can merge (minimizing their surface energy) if the impact is slow and well-centred. But air between them does not always have the time to escape during the shock, so that they can also bounce off each other (Tang, Zhang & Law 2012) -an effect recently exploited to generate levitation of drops on a bath of the same liquid, by shaking the bath at high enough frequency and acceleration (Couder et al 2005).…”
Section: Introductionmentioning
confidence: 99%